THE SIGNIFICANCE OF THE MUSICAL HERITAGE OF EASTERN SCHOLARS IN DEVELOPING THE PROFESSIONAL COMPETENCE OF FUTURE DIRECTORS - Jahongir Mamatqosimov (Bright Mind Publishing, 2025)
This article explores the importance of musical art, particularly the musical heritage of Eastern scholars, in the development of professional competence among future directors. It examines how the musical legacy of such eminent figures as al-Farabi, Ibn Sina, Jami, Navoi, and Babur contributes to shaping the musical thinking of prospective directors.
Keywords: Culture, art, music, director, professional component, musical thinking, musical heritage.